Duration mismatch negativity under varying deviant conditions in individuals with high schizotypal traits - Deng, Jue; Zhang, Yuanjun; Lu, Liqin; Ou, Yuanhua; Lai, Xianghui; Chen, Siwei; Ye, Yiduo (Frontiers in Psychiatry, 2024)
Background Although impaired auditory mismatch negativity (MMN) has consistently been found in individuals with schizophrenia, there are few and inconsistent reports on nonclinical individuals with schizotypy. To date, no studies have thoroughly assessed MMN with different degrees of deviant oddballs in nonclinical schizotypal samples. The aim of this study was to examine the extent of duration MMN (dMMN) amplitudes under two deviant duration conditions (large and small) in nonclinical participants with high schizotypal traits.Methods An extreme-group design was utilized, in which 63 participants from the schizotypy and control groups were selected from a pool of 1519 young adults using the Schizotypal Personality Questionnaire (SPQ). MMN was measured using passive duration oddball paradigms.Basic demographic information and musical backgrounds were assessed and matched, while depression and anxiety were evaluated and controlled for. The repeated measures analysis of covariance was utilized to evaluate differences in dMMN between groups. The Bonferroni correction was applied for multiple comparisons. Partial correlation and multiple linear regression analyses were conducted to investigate the association between dMMN amplitudes and SPQ scores.The amplitudes of dMMN at Cz were significantly increased under the large deviance condition in nonclinical schizotypal individuals (F = 4.36, p = .04). Large-deviance dMMN amplitudes at Fz were positively correlated with mild cognitive-perceptual symptoms in the control group (rp = .42, p = .03). However, as schizophrenia-like symptoms worsened and approached the clinical threshold for schizophrenia, small-deviance dMMN amplitudes at Cz showed negative associations with the cognitive-perceptual factor in the schizotypy group (rp = -.40, p = .04).These results suggest the importance of considering the degree of deviation in duration when implementing the auditory oddball paradigm among nonclinical participants with schizotypal traits. In addition, our findings reveal a potential non-linear relationship between bottom-up auditory processing and the positive dimension of the schizophrenia spectrum.